Pola Asuh Orang Tua Terhadap Pemberian Makan Pada Anak Usia Sekolah Dasar di Desa Binaus - Priska V.G. Suratman; R.L.N.K. Retno Triandhini; Arwyn W. Nusawakan (Journal of Health (JoH), 2018)
Elementary school children are one of the group that can easily get malnutrition because of some factors such as low economic level of the family, unbalanced food nutrition, and lack of knowledge of the parents. A good nutrition status of children is affected by parenting system because children need supervision from the parents for their nutrition needs. Parenting system is a form of interaction in which the parents pay their attention on their children's needs especially for the children's growth process. The purpose of this research is to find out which parenting systems that are applied toward feeding their elementary school children at Binaus Village. This research used quantitative descriptive method with the total participants were 117 parents of 146 children. Questionnaire was used to collect the data. Data analysis used was univariat and the result showed that the majority of mother at Binaus Village, district of Mollo Tengah (Central Mollo), Timor tengah Selatan, East Nusa Tenggara Province, applied authoritative parenting system (79,5%). Although the parents have less amount of income and lack of educational background, the application of authoritative parenting system at Binaus Village is high.